SISTEM INFORMASI MANAJEMEN KOMANDO TANGGAP DARURAT BENCANA LETUSAN GUNUNG MERAPI - , LINDUNG SISWANTO ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Geographically Indonesia is an archipelago that lies at the confluence of four tectonic plates, the Asian Plate, Australian Continent, the plates of the Indian Ocean and Pacific Ocean. On the southern and eastern Indonesia are volcanic belts (volcanic arc) that extends from the island of Sumatra - Java - Nusa Tenggara - Sulawesi, the sides of old volcanic mountains and lowlands in part dominated by swamps. These conditions are potentially vulnerable to a disaster as well as volcanic eruptions, earthquakes, tsunamis, floods and landslides. One of the disasters that occurred in Indonesia, especially in Special Region of Yogyakarta is the eruption of Mount Merapi, which occurred since October 26, 2010. As of early 2012, the impact of the eruption of Mount Merapi in the form of cold lava flood is still prevalent in many areas along the watershed that includes Central Java and Yogyakarta. To cope with the impact of this eruption takes a disaster management that includes several stages: the emergency phase of reconstruction and rehabilitation, preventive stage and mitigation and preparedness phases.Disaster management should be supported by a disaster management information system sufficient to provide optimal support for the management of disaster management that are running. In an effort to cope with this disaster required the participation of the public and all interested parties. One form of disaster management efforts, especially in the emergency response was the establishment of Disaster Emergency Response Command, hereinafter referred to as Command. This command has an important role, especially in terms of providing information include mapping the situation, data disaster victims, volunteers of data, data and information aid donors who provide aid.